Peran Tokoh Adat dalam Membantu Penyelesaian Sengketa Perbatasan Darat antara Indonesia dan Timor Leste di Wilayah Enclave Oecussi - Sudika Mangku, Dewa Gede; APHA, Journal Manager (Asosiasi Pengajar Hukum Adat (APHA) Indonesia, Fakultas Hukum Universitas Trisakti - Jakarta Barat, Indonesia, 2018)
Indonesia has land and sea borders with ten neighboring countries. The basis of the land border law between Indonesia and Timor Leste was the Convention for the Demarcation of Portuguese and Dutch Dominions on the Island of Timor 1904 (Treaty 1904) and the Permanent Court of Arbitration (PCA) of 1914. This was the legacy of the Dutch and Portuguese Governments, where at that time the Dutch and Portuguese had divided Timor Island into two, namely West Timor based in Kupang and East Timor, based in Dili, including the Oecussi enclave which was within the territory of Indonesian sovereignty. The main problem in this study is how the role of traditional leaders in helping to resolve land border disputes between Indonesia and Timor Leste in the Oecussi enclave. After in-depth studies, it was found that in the 1914 Treaty of 1904 and PCA it was stated that the Dutch controlled the Maucator region and the Portuguese controlled the Oecussi enclave area, therefore automatically the inheritance of the colonial period was attached to Timor Leste including the Oecussi enclave. Indonesia and Timor Leste still leave border issues in the Noel Besi, Bidjael Sunan, and Subina regions. The two countries continue to negotiate and negotiate to resolve the issue immediately by forming a Joint Border Committee (JBC) with the aim of accelerating the process of resolving boundary disputes faced. Based on the 2005 Provisional Agreement Article 6 point (b) which implies that local people in this case indigenous peoples/traditional leaders on the border are given space to be involved in the dispute resolution process that occurs at the borders of the two countries by promoting peaceful and nonviolent methods in accordance with Article 8 of the Provisional Agreement in 2005, that the people who inhabit Western Timor (Indonesia) with the people who inhabit East Timor (Timor Leste) have the same socio-cultural background, then it can be ascertained that the customary law that applies in these two groups of people the same. The substance of the customary law can regulate land issues, as well as customary territorial boundaries, the potential of Customary Leaders can actually play a role in negotiating to resolve the issue.